Surface dual-network composite hydrogel with imitated insect three-layer structure, preparation method of surface dual-network composite hydrogel and repeatable programming bionic deformation application of surface dual-network composite hydrogel

The three-layer hydrogel structure with graphene-containing polyacrylamide and poly(N-isopropylacrylamide/sodium methacrylate layers addresses the limitations of single-mode hydrogels by enabling reproducible photothermal and pH-responsive deformations, enhancing applications in bionic actuators and sensors.

CN119219942AActive Publication Date: 2024-12-31HAINAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410957934.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2024-12-31
Estimated Expiration
2044-07-17

AI Technical Summary

Technical Problem

Existing stimuli-responsive deformation hydrogels have limited programmable driving modes and require labor-intensive reprogramming for different deformation properties, hindering their broader applications.

Method used

A surface double-network composite hydrogel with a three-layer structure imitating a flatworm, comprising a graphene-containing polyacrylamide hydrogel matrix layer and poly(N-isopropylacrylamide) and poly(sodium methacrylate) gel network thin layers, allowing for reproducible photothermal and pH-responsive deformations.

Benefits of technology

Enables programmable and repeatable complex deformations through adjustable initial shapes and real-time conductivity sensing, facilitating applications in bionic actuators and drive-self-sensing systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219942A_ABST
    Figure CN119219942A_ABST
Patent Text Reader

Abstract

The invention discloses a surface double-network composite hydrogel with an imitated clam three-layer structure, which comprises a graphene-containing polyacrylamide hydrogel matrix layer, a poly (N-isopropylacrylamide) gel network thin layer is formed on one side of the graphene-containing polyacrylamide hydrogel matrix layer, and a sodium polymethacrylate gel network thin layer is formed on the other side of the graphene-containing polyacrylamide hydrogel matrix layer. Gel double-network structures with photo-thermal response and pH response are respectively formed on the epidermis on the two sides of the matrix gel, just like the body structure of the insect with the body wrapped by the back skin and the abdominal skin in the nature, and different initial shapes can be presented by adjusting the pH; therefore, various different photo-thermal response complex driving modes are endowed under different initial shapes, and finally photo-thermal response complex deformation capable of being repeatedly programmed is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to functional polymer materials, in particular to a surface double-network composite hydrogel imitating a flatworm three-layer structure, a preparation method thereof and a repeatably programmable bionic deformation application. Background Art

[0002] Stimuli-responsive deformation hydrogels are a very promising class of intelligent bionic materials, with very broad application prospects in the fields of soft robots, biomedical devices, artificial muscles, intelligent multifunctional valves, flexible sensors, etc. The research on complex deformation of stimuli-responsive deformation hydrogels initially focused on the development of a single driving mode. Such hydrogels can produce a predetermined deformation under specific external stimuli. Although such hydrogels with a single driving mode perform well in some application scenarios, their functions are relatively limited. With the development of technology and the increase in application needs, the design of stimuli-responsive deformation hydrogels has begun to develop in the direction of more complex and regulated driving modes. Such hydrogels can obtain a rich variety of stimuli-responsive types and various deformation designs. In particular, in recent years, based on the construction of anisotropic structures (such as oriented structures, gradient structures, layered structures, and patterned structures, etc.), the complex deformation of stimuli-responsive deformation hydrogels can be programmed and designed, which can achieve more complex, diverse and controllable bionic deformation functions. However, the programming design of the complex deformation of this stimulus-responsive deformation hydrogel is completed when the gel is formed, so it can only be programmed once. If different complex deformation properties are required, reprogramming and preparation of new gel are required, which is time-consuming and labor-intensive, and seriously limits its further application. Summary of the invention

[0003] In view of this, the present invention provides a surface double-network composite hydrogel with a three-layer structure imitating a flatworm, which solves the problems of the existing stimulus-responsive deformation hydrogel having a relatively single deformation mode and poor repeatable programmable driving performance.

[0004] On one hand, the present invention adopts a surface double-network composite hydrogel with a three-layer structure imitating flatworms, including a graphene-containing polyacrylamide hydrogel matrix layer, wherein the graphene-containing polyacrylamide hydrogel matrix layer forms a poly (N-isopropylacrylamide) gel network thin layer on one side and a poly (sodium methacrylate) gel network thin layer on the other side.

[0005] Preferably, the thickness of the graphene-containing polyacrylamide hydrogel matrix layer is 0.5±0.05 mm, and the thickness of the poly (N-isopropylacrylamide) gel network thin layer and the poly (sodium methacrylate) gel network thin layer are both 0.1±0.01 mm.

[0006] On the other hand, the present invention adopts a method for preparing a surface double-network composite hydrogel with a three-layer structure imitating flatworms, comprising the following steps: placing a graphene-containing polyacrylamide hydrogel matrix layer in a poly (N-isopropylacrylamide) prepolymer solution, allowing it to stand and soak for a period of time, then taking it out and placing it in a mold, subjecting one side of the matrix layer to a first ultraviolet light polymerization, taking it out after the polymerization, washing it, drying it, and then placing it in a sodium polymethacrylate prepolymer solution, allowing it to stand and soak for a period of time, then taking it out and placing it in a mold, and subjecting the other side to a second ultraviolet light polymerization to obtain a hydrogel with a structure imitating flatworms.

[0007] Preferably, the two UV polymerization times are both 15 minutes.

[0008] Preferably, the graphene-containing polyacrylamide hydrogel matrix layer is prepared by the following method: 200 mg of acrylamide and 8 mg of N,N-methylene acrylamide are weighed and placed in 2 mL of a water-soluble graphene dispersion with a mass concentration of 0.5 wt%, mixed evenly and placed in a refrigerator for refrigeration, and then 140 μL of ammonium persulfate solution with a mass concentration of 4.0 wt% and 14 μL of tetramethylethylenediamine are added to the mixed solution, and after rapid shaking, the mixture is injected into a mold, sealed and polymerized at 4°C for 2 h to obtain the graphene-containing polyacrylamide hydrogel matrix layer.

[0009] Preferably, the poly (N-isopropylacrylamide) gel prepolymer solution comprises 3000 mg of N-isopropylacrylamide, 120 mg of N,N-methyleneacrylamide, 120 mg of azobisisobutylamidine hydrochloride and 30 mL of deionized water.

[0010] Preferably, the sodium polymethacrylate prepolymer solution comprises 1285.5 mg acrylamide, 214.5 mg sodium methacrylate, 45 mg N,N-methylene acrylamide, 30 mg azobisisobutylamidine hydrochloride and 30 mL deionized water.

[0011] On the other hand, the present invention also provides an application of a flatworm-mimicking three-layer structure surface double-network composite hydrogel in the preparation of a reprogrammable photothermal response complex deformation actuator.

[0012] On the other hand, the present invention also provides an application of a flatworm-mimicking three-layer structure surface double-network composite hydrogel in the preparation of a complex bionic drive-self-sensing dual-function synergistic actuator.

[0013] According to the method provided by the present invention, water-soluble graphene-polyacrylamide (PAAM-G) composite hydrogel is used as the matrix. Based on the high light absorption efficiency of graphene, the ultraviolet light in the gel is attenuated sharply. When the UV-polymerized gel second network is formed, only a thin layer can be formed on the surface of the matrix. Thus, two different second gel networks of poly N-isopropylacrylamide (PNIPAM) and sodium polymethacrylate (PMAA-Na) can be formed on both sides of the matrix gel, respectively. Thus, a gel double network structure with photothermal response and pH response is formed on the epidermis on both sides of the matrix gel, just like the body structure of flatworms in nature where the dorsal skin and ventral skin sandwich the body. Different from the existing deformation hydrogels whose initial shape cannot be changed after gelation, the "flatworm-like structure" hydrogel can present different initial shapes based on adjusting pH, thereby giving it various photothermal response complex driving modes under different initial shapes, and finally realizing a reproducible photothermal response complex deformation.

[0014] Furthermore, the surface double-network composite hydrogel FLH of the present invention with a three-layer structure imitating flatworms can change its conductivity in real time during the deformation process. The deformation process of the gel can be sensed and presented in real time by its own electrical signals. Therefore, it can be used in a bionic complex drive-self-sensing dual-function collaborative actuator. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the preparation of the "flatworm-like structure" hydrogel (FLH) of the present invention;

[0016] Figure 2 (a) The transmittance of 0.5 mm thick PAAm-G hydrogels with different graphene contents at different wavelengths; (b) The transmittance of PAAm-G hydrogels with different thicknesses and different graphene contents under 365 nm ultraviolet light;

[0017] Figure 3 (a) Surface morphology of PAAm-G; (b) Surface morphology of the side containing PNIPAM; (c) Surface morphology of the side containing PMAA-Na;

[0018] Figure 4 is the scanning electron microscopy image of the cross section of FLH hydrogel;

[0019] Figure 5 (a) Raman white light image and (b) Raman spectral imaging of the cross section of FLH hydrogel;

[0020] Figure 6 (a) The contact angle change curves of the two surfaces of FLH hydrogel (FLH-1 contains PNIPAM surface, FLH-2 contains PMAA-Na surface); (b) The contact angle change curve of PAAm-G hydrogel;

[0021] Figure 7 (a) Schematic diagram of equilibrium bending shape and angle at different pH values; (b) Graph of equilibrium bending angle at different pH values; (c) Cyclic test between pH=2 and pH=12 (scale bar is 5 mm);

[0022] Figure 8 (a) Equilibrium swelling angles at different temperatures under initial conditions of pH = 4.6; (b) bending process in 40°C hot water; (c) recovery process in 20°C cold water (scale bar is 5 mm);

[0023] Fig. 9 FLH hydrogel at pH = 4.6 and 8W / cm 2 (a) Bending and (b) recovery process under NIR irradiation; FLH hydrogel at 2 W / cm 2 (c) Bending and (d) recovery process under NIR irradiation (scale bar is 5 mm);

[0024] Fig.10 Schematic diagram of the “putting down” process of the “flatworm-like structure” hydrogel (FLH) in the smart delivery system (scale bar is 5 mm);

[0025] Fig.11 This is the current change amplitude curve of FLH hydrogel during the “lifting” process (scale bar is 1 cm). DETAILED DESCRIPTION

[0026] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0027] The chemical raw materials used in the embodiments of the present invention are shown in Table 1.

[0028] Table 1 Raw materials details

[0029]

[0030]

[0031] Embodiment 1: A method for preparing a surface double-network composite hydrogel with a three-layer structure imitating a flatworm, comprising the following steps:

[0032] Preparation of S101 matrix hydrogel:

[0033] Weigh AAm (monomer, 200 mg) and BIS (cross-linking agent, 8 mg) and place them in 2 mL of a water-soluble graphene dispersion with a mass concentration of 0.5 wt% after dilution. Mix well and place it in a 4 ° C refrigerator. Then add 140 μL of ammonium persulfate solution (oxidant, 4.0 wt%) and 14 μL of TEMED (reducing agent) to the mixed solution. After rapid shaking, inject it into a mold that has also been refrigerated at 4 ° C and placed with 0.5 mm thick silicone rubber. After sealing, perform low-temperature polymerization in a 4 ° C refrigerator layer for 2 hours. After the polymerization process is completed, soak it in a large amount of deionized water for 24 hours, and obtain graphene-containing polyacrylamide hydrogel (PAAm-G) after washing;

[0034] Preparation of S102 PNIPAM prepolymer solution

[0035] Weigh 3000 mg NIPAM (monomer), 120 mg BIS (cross-linker), 120 mg AIBA (initiator) and 30 mL deionized water, and refrigerate the mixed solution and protect it from light;

[0036] Preparation of S103 PMAA-Na prepolymer solution

[0037] Weigh 1285.5 mg AAm (monomer), 214.5 mg MMA-Na (monomer), 45 mg BIS (cross-linker), 30 mg AIBA (initiator), and 30 mL deionized water, mix them, and refrigerate and protect the mixed solution from light;

[0038] S104 Preparation of "Flatworm-like" Hydrogel (FLH)

[0039] The PAAm-G hydrogel prepared by S101 was placed in the prepolymer solution of PNIPAM and allowed to soak for 6 hours, during which time it was kept away from light. Finally, the PAAm-G hydrogel was taken out and placed in a 0.5mm thick silicone rubber mold, and one side was irradiated with 365nm UV light for 15 minutes. After that, the gel was taken out and placed in a large amount of deionized water for 24 hours to remove unreacted compounds. After taking it out and drying the water, it was placed in the prepolymer solution of PMAA-Na and allowed to soak for 6 hours, during which time it was kept away from light. After that, the soaked gel was placed in a 0.5mm thick silicone rubber mold, and the other side was irradiated with 365nm UV light for 15 minutes. After that, a "flatworm-like structure" hydrogel (FLH) was obtained.

[0040] Example 2: The difference between Example 2 and Example 1 is that in step S101, graphene dispersions of different mass concentrations are added, and a UV spectrophotometer is used to study the gradient transmittance of the graphene content and the thickness of the hydrogel. Figure 2It can be seen in a that when the thickness of PAAm-G is 0.5 mm and the graphene content is 0.1-0.2 wt%, the transmittance is greater than 1% under 365 nm ultraviolet light; when the content is 0.1-0.4 wt%, the transmittance is greater than 1% under 808 nm infrared light. This indicates that at this thickness, a graphene content greater than 0.2 wt% is required to ensure the formation of a thin surface layer of the second gel network. Figure 2 b The transmittance of PAAm-G under 365nm ultraviolet light at various graphene contents and different thicknesses. When the graphene content is 0.5wt%, the transmittance is about 4%, and the thin layer formed is exactly the required thickness. Moreover, at this graphene content, the photothermal conversion effect is also in line with the original driving design. Based on the high light absorption efficiency of graphene, the ultraviolet light in the gel is drastically attenuated. Only a 0.1mm thin layer can be formed on the surface of the substrate during the second network of UV-polymerized gel. Therefore, a water-soluble graphene with a content of 0.5wt% was finally selected.

[0041] Example 3: Characterization test of the "flatworm structure" hydrogel (FLH) prepared in Example 1

[0042] (1) The microstructure of FLH hydrogel was characterized by scanning electron microscopy (SEM). Figure 3 Compared with the PAAm-G matrix gel, the surface micromorphology of the FLH hydrogel shows that the gel double network layers on both surfaces present a denser pore structure than the single network PAAm-G matrix gel, indicating that two different double network gel structures have been formed on the surface of the matrix gel. This indicates that the surface gel double network structure has been successfully obtained. Figure 4 The microscopic morphology of the FLH hydrogel cross-section can be divided into three parts: PAAm and PNIPAM double network thin layer (FLH-1), PAAm network layer (FLH-0) and PAAm and PMAA-Na double network thin layer (FLH-2). It can be observed that the surface layers on the upper and lower sides are about 0.1 mm thick and have a different morphology than other parts, which indirectly proves that the composition of the upper and lower sides has changed. This structural difference gives the FLH hydrogel an anisotropic structure, increases the modulus and driving performance of the FLH hydrogel, and also observes that the network structure from the surface to the inside is in a transitional state, forming a double network gradient structure.

[0043] (2) The cross-section of the FLH hydrogel was analyzed by Raman imaging. Figure 5 The results show that the water-soluble graphene is evenly distributed inside the hydrogel, forming the FLH hydrogel with stable composition in Example 1.

[0044] (3) The contact angles of the two surfaces of FLH hydrogel were tested (FLH-1 contains PNIPAM surface, FLH-2 contains PMAA-Na surface). The results are as follows: Figure 6 , the PMAA-Na gel network decreased from 63° to 39° within 0-8s; while the hydrophilicity on the PNIPAM side was quite different, decreasing from 73° to 71° within 0-8s, with almost no change. The curves of FLH-1 and FLH-2 also further illustrate the difference between the two surfaces, proving the difference in the double network structure of the two surfaces of FLH hydrogel. The two double network surfaces are denser than the gel network of a single matrix hydrogel, so the contact angles of the two surfaces of FLH hydrogel are larger and change more slowly than the matrix hydrogel (PAAm-G).

[0045] (4) Study on pH response properties of FLH hydrogel

[0046] like Figure 7 As shown in a, the same FLH hydrogel (size 2×12×5 mm 3 ) were placed in solutions with different pH values, and after waiting for 2 hours for complete swelling, the central angle of the gel was measured as its equilibrium swelling angle. The results showed that there was an angle of 0° between pH = 4 and 5. Figure 7 b It can be seen that when pH = 4.6, the equilibrium swelling angle is 0° and the shape is a straight strip. When pH <4.6, the FLH hydrogel bends toward the side containing the PMAA-Na second network, and the forward bending can reach 160°; when pH >4.6, the FLH hydrogel bends toward the side containing the PNIPAM second network, and the reverse bending can reach 267°. It can be seen that the various states of the FLH hydrogel under different pH conditions can be used as the initial state for subsequent deformation driving, providing a basis for the programmed design of the initial state of the hydrogel. In addition, the FLH hydrogel was subjected to a cyclic experiment to verify its stability and durability. The same FLH hydrogel (size 2×12×5mm 3 ) was repeatedly placed in solutions of pH = 2 and pH = 12, each time staying in the solution for 1 hour, and after reaching a balanced swelling state, its central angle was measured, and this process was repeated 10 times. Figure 7 As shown in c, after 10 cycle experiments, it can be observed that it can achieve 96% recovery of the initial state, proving that the hydrogel has good durability and stability.

[0047] (5) Thermal response performance test of FLH hydrogel

[0048] When pH = 4.6, FLH hydrogel (size 2 × 12 × 5 mm 3 ) is a straight line, such as Figure 8As shown in a, when the water temperature rises from 20°C to 40°C, the bending angle of the hydrogel changes from 0° to 360°. In addition, the driving and recovery processes of the FLH hydrogel in 40°C hot water and 20°C cold water were recorded respectively. Figure 8 As shown in Fig. b, the FLH hydrogel in 40℃ constant temperature hot water achieves a bending change from 0° to 360° within 80s driven by the thermal contraction of the PNIPAM second network. After the bending drive is completed, the FLH hydrogel is quickly placed in 20℃ constant temperature cold water. During the recovery process, the recovery rate of the FLH hydrogel changes from fast to slow, and finally reaches a balance state ( Figure 8 c).

[0049] (6) Photothermal response performance test of FLH hydrogel

[0050] In order to study the bending and folding properties of FLH hydrogel under the illumination of surface light source and point light source, the following experimental design was designed and carried out. First, a piece of 2×12×5mm 3 The strip FLH hydrogel was used as the experimental sample. Then 2.4W / cm 2 The near-infrared light with the highest illumination intensity, under the full coverage of the near-infrared light, the diameter of the surface light source is 13mm, such as Fig. 9 As shown in a and 9b, the FLH hydrogel, which was initially in a straight strip at pH = 4.6, bends from 0° to 360° in 74 seconds. After the near-infrared light is immediately removed, the FLH hydrogel returns to its initial state in about 170 seconds. After returning to the initial state, the same experimental sample is used and 0.6 W / cm 2 The near-infrared light with a light intensity of 2 mm was used to partially irradiate the test sample. The diameter of the irradiated area was 2 mm. The side containing the PNIPAM second network at the irradiated position began to shrink, while the unirradiated area remained intact, thus showing a bending phenomenon. The bending angle of the FLH hydrogel can change from 0° to 90° in about 25 seconds. Fig. 9 c). When the near-infrared light is removed, the experimental sample can return to its original straight strip shape in about 60 seconds ( Fig. 9 d). This indicates that the prepared FLH hydrogel has excellent photothermal response properties.

[0051] (7) Reprogrammable biomimetic applications of FLH hydrogels

[0052] By utilizing the various initial states of FLH hydrogel that can be repeatedly programmed, various bionic drives can be achieved based on remote control of near-infrared light, such as "releasing", "hooking", "lifting", "pushing" and other bionic actions.

[0053] like Fig.10, when the FLH hydrogel is in the initial state of positive bending, the actions of "putting" and "hooking" can be realized. First, one end of a 1.2mm long FLH hydrogel is fixed so that the entire FLH hydrogel experimental sample is completely immersed in a liquid environment with pH=2. At the same time, a ring-shaped weight is put on the sample, and the weight will be lifted by the hydrogel sample. A high platform is placed directly below it to simulate the scene of taking and putting things. Then use 4.0W / cm 2 The hydrogel is dynamically irradiated with a high-power near-infrared light source (with a light source diameter of 5mm), which requires the hydrogel to be deformed from top to bottom to ensure uniform and effective deformation. When the deformation reaches a certain degree, the heavy object will be put down; when the near-infrared light source is removed, the FLH hydrogel sample will return to its initial state, and the "putting down" action has been completed. It can be observed that in this bionic drive, the deformation rate and recovery rate of the hydrogel are very high, and the action can be completed efficiently.

[0054] (8) Synergistic application of bionic driving and self-sensing of FLH hydrogel

[0055] Based on the basic sensing properties of FLH hydrogel, a device with self-sensing ability for intelligent delivery system was developed to lift or jack heavy objects. Fig.11 When there is no near-infrared surface light source, the initial state of the bionic device is in a reverse bending state. When the surface light source is irradiated, the device begins to deform and lifts the weight. At this time, the resistance will decrease sharply, the amplitude of the current signal fluctuation will increase, and the current signal will be at a peak value. When the near-infrared surface light source is removed, the current will gradually return to the initial state. In this way, based on the change of electrical signals, the driving process of the device can be observed in real time, and the coordination of self-driving and self-sensing can be achieved, realizing the collaborative design and development in the field of flexible sensors in the future.

[0056] In summary, by adopting the preparation method of the "simulated flatworm structure" hydrogel provided by the present invention, with water-soluble graphene-polyacrylamide (PAAm-G) composite hydrogel as the matrix, two different second gel networks of poly N-isopropylacrylamide (PNIPAM) and sodium polymethacrylate (PMAA-Na) can be formed on both sides of the matrix gel, thereby forming a gel double network structure with photothermal response and pH response on the epidermis on both sides of the matrix gel, just like the body structure of flatworms in nature where the dorsal skin and ventral skin sandwich the body. Different from the existing deformation hydrogels whose initial shape cannot be changed after gelation, the "simulated flatworm structure" hydrogel can present different initial shapes by adjusting the pH, thereby giving it various complex photothermal response driving modes under different initial shapes, and finally realizing a repeatable and programmable photothermal response complex deformation.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A surface double-network composite hydrogel imitating a three-layer structure of flatworms, characterized in that: The invention comprises a graphene-containing polyacrylamide hydrogel matrix layer, wherein one side of the graphene-containing polyacrylamide hydrogel matrix layer forms a poly-N-isopropylacrylamide gel network thin layer, and the other side forms a poly-sodium methacrylate gel network thin layer.

2. The surface double-network composite hydrogel with a three-layer structure imitating flatworms according to claim 1, characterized in that: The thickness of the graphene-containing polyacrylamide hydrogel matrix layer is 0.5±0.05 mm, and the thickness of the poly (N-isopropylacrylamide) gel network thin layer and the poly (sodium methacrylate) gel network thin layer are both 0.1±0.01 mm.

3. A method for preparing a surface double-network composite hydrogel imitating a three-layer structure of flatworms, characterized in that: The method comprises the following steps: placing a graphene-containing polyacrylamide hydrogel matrix layer into a poly (N-isopropylacrylamide) prepolymer solution, allowing it to stand and soak for a period of time, then taking it out and placing it in a mold, subjecting one side thereof to a first ultraviolet light polymerization, taking it out after the polymerization, washing it, drying it, and then placing it into a sodium polymethacrylate prepolymer solution, allowing it to stand and soak for a period of time, then taking it out and placing it in a mold, and subjecting the other side thereof to a second ultraviolet light polymerization to obtain a flatworm-like structure hydrogel.

4. The method for preparing a surface double-network composite hydrogel with a three-layer structure imitating a flatworm according to claim 3, characterized in that: The UV polymerization time for both times was 15 min.

5. The method for preparing a surface double-network composite hydrogel with a flatworm-like three-layer structure according to claim 3, characterized in that: The graphene-containing polyacrylamide hydrogel matrix layer is prepared by the following method: 200 mg of acrylamide and 8 mg of N,N-methyleneacrylamide are weighed and placed in 2 mL of a water-soluble graphene dispersion with a mass concentration of 0.5 wt%, and the mixture is evenly mixed and placed in a refrigerator for refrigeration. Then, 140 μL of ammonium persulfate solution with a mass concentration of 4.0 wt% and 14 μL of tetramethylethylenediamine are added to the mixed solution, and after rapid shaking, the mixture is injected into a mold, sealed, and polymerized at 4°C for 2 h to obtain the graphene-containing polyacrylamide hydrogel matrix layer.

6. The method for preparing a flatworm-mimicking three-layer surface double-network composite hydrogel according to claim 3, characterized in that: The poly N-isopropylacrylamide gel prepolymer solution includes 3000 mg N-isopropylacrylamide, 120 mg N,N-methyleneacrylamide, 120 mg azobisisobutylamidine hydrochloride and 30 mL deionized water.

7. The method for preparing a surface double network composite hydrogel with a flatworm-like three-layer structure according to claim 3, characterized in that: The sodium polymethacrylate prepolymer solution includes 1285.5 mg acrylamide, 214.5 mg sodium methacrylate, 45 mg N,N-methylene acrylamide, 30 mg azobisisobutylamidine hydrochloride and 30 mL deionized water.

8. Application of a surface double-network composite hydrogel with a three-layer structure mimicking that of a flatworm in the preparation of a reprogrammable photothermal responsive complex deformation actuator.

9. Application of a surface double-network composite hydrogel with a three-layer structure imitating that of a flatworm in the preparation of a complex bionic drive-self-sensing dual-function synergistic actuator.

Citation Information

Patent Citations

  • 4D (four-dimensional) printing method of programmable deformation tough hydrogel

    CN108409989A

  • Self-repairing multi-photoresponse double-layer supramolecular hydrogel as well as preparation method and application thereof

    CN112126082A

  • Dual-network hydrogel bionic intelligent skin and preparation method thereof

    CN113427876A

  • Coatable polyacrylamide hydrogel-based high-sensitivity humidity response driver and preparation method thereof

    CN114395148A

  • Triple stimuli-responsive double-layer hydrogel actuator and preparation method thereof

    CN114854046A